The Analysis of Pedestrian Service in Railway Station Area: A Case Tanah Abang Station, Jakarta A Case Tanah Abang Station, Jakarta - Pratama, Andreas; Rifai, Andri Irfan; Thole, Joko (DAS Institute, 2022)
Tanah Abang Station is a means of transportation that is in great demand by traders and buyers by passing through the sidewalk, which is currently used to connect pedestrians to move from one place to another. Due to its strategic location and the middle of the city, many visitors pass by the sidewalk near station. This study analyzes the level of service of sidewalk facilities in the Tanah Abang station environment, where the current facilities are whether analysis method used is Index Performance Analysis (IPA) with a value of Satisfaction and Importance of Pedestrian Facilities in the Tanah Abang station area. From the satisfaction and importance comparison table results, an average satisfaction index of 4.14 was obtained, an average interest index of 3.34, and a gap average of -0.76.